2014
DOI: 10.1021/ct400977r
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Signaling Pathways in Proteins through Network Theory: Importance of the Topology

Abstract: Network theory methods are being increasingly applied to proteins to investigate complex biological phenomena. Residues that are important for signaling processes can be identified by their condition as critical nodes in a protein structure network. This analysis involves modeling the protein as a graph in which each residue is represented as a node and edges are drawn between nodes that are deemed connected. In this paper, we show that the results obtained from this type of network analysis (i.e., signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 62 publications
4
102
0
Order By: Relevance
“…This is usually done based on interresidue distances and correlation coefficients extracted from MD simulations. We have recently shown that this approach introduces significant statistical errors in the analysis, and networks constructed in this way were not able to identify residues important for signal propagation in the protein imidazole glycerol phosphate synthase (21) or discriminate allosterically active mutants of the lactose repressor protein (22). On the other hand, we showed that assigning network edges based on interaction energies extracted from MD simulations can give an accurate description of signal propagation in proteins (21).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…This is usually done based on interresidue distances and correlation coefficients extracted from MD simulations. We have recently shown that this approach introduces significant statistical errors in the analysis, and networks constructed in this way were not able to identify residues important for signal propagation in the protein imidazole glycerol phosphate synthase (21) or discriminate allosterically active mutants of the lactose repressor protein (22). On the other hand, we showed that assigning network edges based on interaction energies extracted from MD simulations can give an accurate description of signal propagation in proteins (21).…”
Section: Introductionmentioning
confidence: 93%
“…These are processed to construct the network topology and extract the interaction energies to assign network edges, following methodology previously introduced (21). Briefly, weights u ij are assigned to different residue pairs as follows:…”
Section: Available Types Of Analysismentioning
confidence: 99%
See 3 more Smart Citations